Professional career aspiration and professionalism among university students: A challenge of professional development in the 21st century - Li, Yimeng (2016)
Universities today play two important roles in the systematic development of future professionals: They influence both the students’ entry into professional careers and the development of professionalism. Yet, the psychology of professional career entry and the development of professionalism among university students are not well-understood. This paper reports an empirical study of the nomological networks professional career motivation and (PCM) and professional attitudes, in relation to several professional outcomes of particular interest during the university education period. Specifically, we ask: can attitudinal professionalism be measured among university students? How is the motivation to pursue professional work related to having professional attitudes among university students? Using data collected from 873 undergraduates pursuing degrees leading toward accounting, teaching, banking and finance professions, we first develop a scale to measure professional attitudes among students. Next, we establish that while PCM better predicts professional career intention among students, professional attitudes are more associated with the students' professional identification and willingness to support transformation of the profession. We conclude that the motivation to be a professional does not necessarily related to having certain professional attitudes among university students and call for more empirical studies to understand the development of professionalism during the university period, particularly regarding to the attitudinal aspect. Research and practical implications of the findings are discussed.